Kajian Analisis Kompetensi Pilot Di Indonesia - Winahyu, Sri Hapsari; Tazkiyah, Tazkiyah (Sekretariat Badan Penelitian dan Pengembangan Perhubungan, 2010)
In the air transport sector, a pilot specially required in order to rontrol the aircraft perfectly to gavepeaceful condition to all stakeholders who enjm; travel and to be trusted to prauide safety and comfortin the process of that journey.In order to realize it is neressary to prauide education and competenct; based -training. In addition tomaintain competence that has been awned btJ a pilot, proficiency test should be done at thetime will extend his license.Keywords : pilot competence